Sustainability in transformation of maternal mortality by interaction based approach in Dairi, Indonesia - Henry Manik; Rika Subarniati Triyoga; M. Fidel G. Siregar; R. Kintoko Rochadi; Sandeep Poddar (SAGE Publishing, 2021)
Introduction: Health and mortality problems are closely related to the maternal mortality rate (MMR). Efforts to reduce MMR have been carried out by many countries, including the Indonesian government. Materials and Methods: This research was conducted using two approaches, namely quantitative and qualitative or mixed methods and 149 respondents and 26 informants, to reduce MMR in Dairi Regency. This study was also carried out to determine the dominant variable that affects mother's behavior in an effort to reduce MMR in accordance with the existing theory. Result: Mother's intention to contribute to the reduction of MMR in this study was influenced by the good factor directly or indirectly. This is indicated by the score p<0.005. The study also shows that it is very important for the health workers to be able to communicate well with individuals and communities. Conclusion: The present study will help to reduce maternal fatalities, and will help to build systems and processes that will allow control the behaviour of the pregnant women and determine the cause of death as well as its contributing factors.